The effectiveness of the 'matahari' method in improving basic arithmetic skills of junior high school students - Sutarman Borean; Sinambela, Mindo Hotmaida; Marlince Anggelina Siep; Risnauli Y. Nainggolan; Tresya Palungan (Journal of Honai Math, 2025)
The persistent disparity in students’ mastery of basic arithmetic concepts presents a critical challenge in mathematics education, particularly in regions with limited pedagogical resources. While traditional approaches often fall short in addressing foundational numerical skills, there is a lack of practical, culturally adaptable methods tailored to early secondary learners. This study introduces the "Matahari" method an acronym for Matematika Hitung Jari as a novel instructional strategy that integrates finger-counting techniques with repetitive practice to enhance arithmetic fluency. The primary aim of this research is to examine the effectiveness of the Matahari method in improving the basic arithmetic skills of seventh-grade students at SMP Biji Sesawi Wamena. Employing a quasi-experimental design with a non-equivalent pretest-posttest control group, the study used random sampling to assign students to experimental and control classes. Validated instruments were utilized for data collection, including tests, questionnaires, observations, interviews, and documentation, while data analysis was conducted using One-Way ANOVA and t-tests. The findings revealed a statistically significant improvement in the arithmetic performance of the experimental group, with an average gain of 14.31 compared to 5.46 in the control group. Moreover, the method received highly favorable responses from both students (87.35%) and teachers (78.33%). These results suggest that the Matahari method holds substantial pedagogical value in enhancing numeracy skills and offers a culturally relevant solution for addressing foundational learning gaps in mathematics.